Satur - Conde, Manuel; Dela Rosa, Jaime; Razon, Delia
Cristina, a pretty young neighborhood girl, is pursued by the mysterious Satur, a wealthy but mysterious young man. Cristina, however, is engaged to Sendong, a young farmer. When Cristina's mother is taken suddenly ill and there appears to be no hope of recovery, Satur says that can cure her in exchange for Cristina being promised to him. Desperate, Cristina agrees and her mother pulls through. Cristina and Sendong soon find out that she may have well made a deal with the devil.--frankfob2@yahoo.com